Gibberellin and auxin signaling genes RGA1 and ARF8 repress accessory fruit initiation in diploid strawberry. Issue 3 (30th December 2020) - Zhou, Junhui; Sittmann, John; Guo, Lei; Xiao, Yuwei; Huang, Xiaolong; Pulapaka, Anuhya; Liu, Zhongchi
Abstract: Unlike ovary-derived botanical fruits, strawberry ( Fragaria x ananassa ) is an accessory fruit derived from the receptacle, the stem tip subtending floral organs. Although both botanical and accessory fruits initiate development in response to auxin and gibberellic acid (GA) released from seeds, the downstream auxin and GA signaling mechanisms underlying accessory fruit development are presently unknown. We characterized GA and auxin signaling mutants in wild strawberry ( Fragaria vesca ) during early stage fruit development. While mutations in FveRGA1 and FveARF8 both led to the development of larger fruit, only mutations in FveRGA1 caused parthenocarpic fruit formation, suggesting FveRGA1 is a key regulator of fruit set. FveRGA1 mediated fertilization-induced GA signaling during accessory fruit initiation by repressing the expression of cell division and expansion genes and showed direct protein–protein interaction with FveARF8. Further, fvearf8 mutant fruits exhibited an enhanced response to auxin or GA application, and the increased response to GA was due to increased expression of FveGID1c coding for a putative GA receptor. The work reveals a crosstalk mechanism between FveARF8 in auxin signaling and FveGID1c in GA signaling. Together, our work provides functional insights into hormone signaling in an accessory fruit, broadens our understanding of fruit initiation in different fruit types, and lays the groundwork for future improvement of strawberry fruit productivity and quality. Abstract : An investigation of the mechanism of accessory fruit initiation in diploid strawberry, identifying the function of two hormone signaling genes in fruit initiation.